1984
DOI: 10.1063/1.95056
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution in a plasma erosion opening switch

Abstract: The current distribution in a plasma erosion opening switch is determined from magnetic field probe data. During the closed state of the switch the current channel broadens rapidly. The width of the current channel is consistent with a bipolar current density limit imposed by the ion flux to the cathode. The effective resistivity of the current channel is anomalously large. Current is diverted to the load when a gap opens near the cathode side of the switch. The observed gap opening can be explained by erosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 8 publications
(1 reference statement)
0
21
0
Order By: Relevance
“…Early theories characterizing the plasma pushing by the force and describing the magnetic field penetration by classical diffusion disagree with observations. Noticeably, observations have shown rapid magnetic field penetration much faster than predicted by classical diffusion based on the plasma resistivity [11]- [15]. Other theories [16]- [18] have shown that nonuniformity in the plasma, giving rise to a varying Hall electric field, may result in an enhanced magnetic field penetration.…”
mentioning
confidence: 94%
“…Early theories characterizing the plasma pushing by the force and describing the magnetic field penetration by classical diffusion disagree with observations. Noticeably, observations have shown rapid magnetic field penetration much faster than predicted by classical diffusion based on the plasma resistivity [11]- [15]. Other theories [16]- [18] have shown that nonuniformity in the plasma, giving rise to a varying Hall electric field, may result in an enhanced magnetic field penetration.…”
mentioning
confidence: 94%
“…Previous experimental investigations showed two main phenomena: a fast magnetic field penetration through the entire plasma [4], [5] and a fast increase of the switch impedance [1], [2]. The first phenomenon is explained within the framework Manuscript received August 7, 1997; revised December 15, 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Fast increase of the POS impedance is assumed to be associated with the anomalous fast magnetic field penetration [4] and the formation of a nonneutral layer [10] in the vicinity of the cathode or inside the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma opening switch is a laboratory device designed to provide the appropriate power conditioning for inductive, pulsed, high-power generators [8,9,10,13,14,17]. A schematic of an opening switch is shown in Fig.…”
Section: Plasma Opening Switchmentioning
confidence: 99%
“…The theory has been successfully applied to the structuring of sub-Alfvénic plasma expansions [1,2,3,4,5,6,7] and to rapid magnetic field transport in plasma opening switches [8,9,10,11,12,13,14,15,16,17]. In recent years it has become evident that Hall physics plays a critical role in magnetic reconnection processes [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36] and this has spurred renewed interest in this subject.…”
Section: Introductionmentioning
confidence: 99%